Experiences and Expectations of the CompañíaNacional de Fuerzay Luz on Payments for Environmental Services - Montero, Marco (2010)
The monetary recognition from different kinds of environmental services on behalf of their providers is a mechanism to assure their continuity over time. In Costa Rica there is a great experience on how to pay for environmental services, being CNFL one of the institutions that had developed these mechanisms for many years. The traditional schemes of payment for environmental services (PES) have evolved into more striking systems of recognition; nowadays environmental services provided by agro-ecosystems are also recognized, whenever developed through environmentally sustainable practices, searching for ecologic improvement in the areas where implemented. Furthermore, the recognition of environmental services in different areas such as the promotion of tree planting activities in the cities searching for the improvement of urban ecosystems are being considered as well. There are still important challenges to solve, being one of the most important to establish and to validate some indicators, as well as evaluation and measurement methods to assess the real impact of PES activities on the environment.